ANALISIS DAMPAK LALU LINTAS AKIBAT PEMBANGUNAN WISATA ALAM DESA MEDOWO KECAMATAN KANDANGAN KEDIRI - Nurunnafissa, Maulida; Rijanto, Tri; Amudi, Abdiyah (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
Medowo village is one of the villages in Kandangan Districts residing in hilly area. Geographicalcircumstances make the Medowo Village has a variety of picturesque hills land and fertile. Some of which arenature tourism, nature tourism Gandrung Hill, Plengsengan Refreshing Hill (PRH), and Waterfall Sumber Jodo.The existence of the tourism traffic flow increasing at rush-hour. Lack of supporting facilities infrastructurearound natural tourism makes the reduced comfort felt by road users.To find out the impact of traffic on the roads of the third, then conducted the research along with trafficperformance analysis using the method of MKJI 1997 and the Balanced Scorecard SWOT analysis. From theresults of the calculation of the performance of the traffic road of in the third obtained the results of A road levelof service or Level Of Service (LOS) worth 0.02 - 0.03 impact analysis using SWOT and Balanced Scorecardrefers to the four (4) criteria i.e. strengths, weaknesses, opportunities, and threats. Keywords: Impact of traffic, Tourism nature, Capacity, Service levels